Respons karakteristik agronomi, fisiologi, dan biokimia padi (Oryza sativaL.) tercekam salinitas dengan umur bibit berbeda: The agronomic, physiology, and biochemical characteristics responses of paddy (Oryza sativa L.) stressed by salinity with the different seed ages - Nasrudin, Nasrudin; Isnaeni, Selvy (AGROMIX, 2022)
Introduction: Salinity is a major constraint in rice crop production through inhibiting the absorption of water and minerals. The seedling age optimally can increase the adaptability of plants under saline conditions. The objective of this study was to examine the agronomic, physiological, and biochemical responses of rice under saline conditions using the different seed age to determine their adaptability to the abiotic stress. Methods: The study used a CRD non-factorial, there is seedling age with three levels including 21, 28, and 35 days after sowing (DAS). The study used rice cv. Banyuasin and salinity stress given is NaCl with the concentration 8 dS m-1. The addition of NaCl when the plants were 12 and 54 days after planting (DAP). Results: The different seed age planted under saline conditions significantly affects to agronomic and physiological characteristics as indicated by shoot dry weight, plant biomass, and chlorophyll content. The different seed age planted under saline conditions significantly affects biochemical characteristics as indicated by proline content and nitrate reductase activity. The rice seedling age of 21 DAS produced the highest biomass and shoot dry weight, the rice seedling age of 28 DAS produced the highest chlorophyll content and nitrate reductase activity, and the rice seedling age of 35 DAS produced the highest proline content. Conclusion: The older rice seedling (35 DAS) increased the higher proline content, while the younger rice seedling (21 DAS) increased the shoot dry weight and plant biomass. In addition, rice seedlings (28 DAS) produced the highest chlorophyll content and nitrate reductase activity.